500 General practitioners' views on the electronic transfer of prescriptions to pharmacies in Ireland: a qualitative interview study. (13th April 2023) - Mahon, C; Clein, J; Dalton, K
Abstract: Introduction: The use of electronic systems to transfer prescriptions continues to grow in healthcare systems worldwide. In response to the COVID-19 pandemic, legislation was implemented in Ireland in April 2020 to permit the electronic transfer of prescriptions (ETP) from prescribers to pharmacies using a national secure email system (Healthmail). This has resulted in a significant increase in the volume of prescriptions transmitted via Healthmail from general practitioners (GPs) to pharmacies in Ireland. Aim: With a clear need to evaluate how stakeholders have been affected by this initiative and to guide the future delivery of patient care, the primary aim of this study was to investigate GPs' views on the ETP to pharmacies in Ireland via Healthmail and how it has affected their practice. Methods: Semi-structured interviews were conducted via video-conference with GPs in Ireland. GPs were identified using convenience and snowball sampling, purposively ensuring variety in age/years of experience, gender, and practice location. Interviews were audio-recorded and transcribed verbatim . Interview transcripts underwent thematic analysis (1). Results: Twelve audio-recorded interviews were conducted with GPs between May 2021 and July 2021. The participants had a median of 16 years' experience as a GP. Four main themes were generated: 1)Efficiencies with prescribing and easing GP workload: even with limited training, GPs felt that Healthmail's ETP has been easy to use and seamlessly integrated into their practice. Time has been saved and overall workload decreased due to less prescription printing and delegating more to administrative staff with prescription ordering. 2) New GP-pharmacist communication pathways: GPs found asynchronous communication regarding prescription queries less disruptive to their workflow, and particularly useful for less urgent matters. Some GPs were not aware of some Healthmail functions that facilitated additional notes between GPs and pharmacists, whilst others were concerned they had no evidence if pharmacists saw these notes. 3) Security, transparency, and documentation: whilst acknowledging their lack of technological expertise, GPs perceived that Healthmail prescriptions had security advantages over physical ones overall; the increased transparency of the prescription journey minimises the risk of prescriptions being mislaid, damaged, or fraudulently altered, as well as creating an audit trail. 4) Implications for patients: ETP via Healthmail has reduced footfall to practices, reduces multiple pharmacy use, and most patients have adapted well to it. GPs were mostly reluctant to engage routinely in any hypothetical bidirectional communication with patients via Healthmail. Conclusion: This study provides strong evidence for continuing the ETP to pharmacies in Ireland as GPs found this initiative easy to use, time-saving, and enhancing both GP-pharmacist communication and GP workflow. However, this study has highlighted stakeholders' lack of awareness with some functions of Healthmail, so any future systems utilised for the ETP should come with best-practice guidance for all users. While the purposive sampling facilitated GP heterogeneity, snowball sampling may have somewhat reduced the diversity in views; a future survey would be useful in identifying if any GPs characteristics significantly influencing GPs' views, as well as identifying other issues experienced and novel ideas to improve the ETP process going forward. References: 1. Braun V, Clarke V. Using thematic analysis in psychology. Qualitative research in psychology. 2006 Jan 1;3(2):77-101.